Effective Strategies to Enhance Social Media Marketing - Haj, Imad (Digital Repository of Theses - SSBM Geneva, 2025)
Despite the positive impacts of social media marketing on organizations, some researchers have reported that ineffective use of social media may expose organizations to losses both financial and data. The purpose of this study was to understand the effective and ineffective social media marketing strategies that may improve business and organizational performance but also lead to business failure. A qualitative explanatory single case study design was used in this study. Data was collected through interviews with a sample of seven business leaders. The study results addressed the research problem by identifying different strategies that can be used by leaders to prevent business failure and improve organizational performance, including social media influencer partnerships, sharing timely and exciting content, storytelling about the experience with services or products, and utilizing video content, as well as promoting relevant, highquality content to help businesses access a wider audience. The findings can help leaders and organizations understand effective strategies to prevent business failures. Business policymakers can use the current findings to develop effective policies to promote social media marketing and enhance business performance. Future research may replicate this study using quantitative methods and a larger sample size to examine the relationship between influencer partnerships and business performance.